The determinant factors that contribute the purchasing of Medical and Health Insurance (MHI) by consumers in Subang Jaya, Selangor / Nor Haslinda Abd Rasid - Abd Rasid, Nor Haslinda (Faculty of Business and Management, 2015)
Medical and Health Insurance (MHI) is a very important tool to secure family member or individuals as well as to provide compensation or security financial for individual once admitted in private hospital cause by injury, sickness or doing any treatment. However, in Malaysia the purchasing of MHI is yet not preferable. Recently, medical expenses increase critically but there are still a lot of Malaysian do not have their own Medical and Health Insurance (MHI). The researcher conducting this research in order to find out and contribute ideas on the determinant factors that contribute the purchasing of MHI. The crucial goal of conducting this paper is to analyse the dominant factor that influence the purchasing of Medical and Health Insurance (MHI). Therefore, this study come out with three independent variable which are social influence, knowledge and income. Based on the analysis, social influence, knowledge and income have a significant relationship with Medical and Health Insurance (MHI).